Salvage esophagectomy after failure of definitive radiochemotherapy for esophageal cancer. Issue 7 (25th October 2016) - Farinella, Eleonora; Safar, Adonis; Nasser, Haydar A.; Bouazza, Fikri; Liberale, Gabriele; Paesmans, Marianne; Marechal, Raphael; Van Laethem, Jean‐Luc; Hendlisz, Alain; VanHoutte, Paul; El Nakadi, Issam
Abstract : Background: Definitive radiochemotherapy (dRCT) in locally advanced esophageal cancer is associated with a high rate of loco‐regional recurrence. In this condition, salvage esophagectomy may be considered as a therapeutic option. The aim of this analysis is to evaluate the feasibility and the morbi‐mortality of this strategy. Methods: Between January 2006 and April 2014, 208 patients underwent esophagectomy for esophageal cancer at ULB‐Erasme‐Bordet. Thirty‐two patients received a preoperative radiochemotherapy (pRCT) followed by planned esophagectomy (Group 1) for locally advanced disease. Sixteen patients underwent salvage esophagectomy for recurrence or failure after dRCT (Group 2). Data on post‐operative morbidity and mortality and survival were collected and analyzed. Results: An increase of overall morbidity was detected in Group 2 as compared to Group 1 (43% vs. 37.5%), mainly related to respiratory complications (35.5% vs. 28%) and anastomotic leak (25% vs. 3%). No 90‐days mortality was observed in the two surgical groups. The 1, 2, and 3‐year survival rates after surgery were respectively 89%, 80%, and 71% for Group1 and 84%, 73%, and 63% for Group 2. Conclusions: In our experience, both salvage esophagectomy and esophagectomy after pRCT showed good survival results with low postoperative morbidity and mortality. Salvage surgery remains a therapeutic indication in selected patients. J. Surg. Oncol. 2016;114:833–837 . © 2016 2016 Wiley Periodicals, Inc.